Student Learning Outcomes With The Student Teams Achievement Division (Stad) Learning Model At Sman 3 Jember On The Material On The Theory Of The Formation Of The Universe - Umi Fauziah (Pusat Riset dan Inovasi Nasional, 2023)
Educational problems always arise along with the development and increase of students' abilities, situations and environmental conditions that exist due to the influence of information and culture as well as the development of science and technology. The geography subject for the material of the Theory of the Formation of the Universe according to the results of observations and interviews made to class X social studies 3 students at SMAN 3 Jember is considered boring material. This study used the classroom action research method. The research will be carried out as many as two cycles, if in cycle I it has been achieved as desired, namely achieved classical completeness, then the implementation of the cycle is stopped, but if the results achieved have not reached the desired one, then continued in cycle II by optimizing the researcher's hard work in applying the STAD learning model so that the expected goals are achieved. The results of learning activities in cycle II are better than learning in cycle I. The application of the STAD model learners has succeeded in increasing students' abilities and increasing student activity by 93.75%, growing awareness to always uphold cooperation in solving problems together so as to realize a high social sense between friends in school